Effect of land disposal of stillage on the leaching of soil nutrients. III. Potassium, calcium and magnesium - Nunes, Marcos R.; Leal, Jair R.; Velloso, Ary Carlos X. (Pesquisa Agropecuaria Brasileira, 2014)
The effect of increasing doses of water in the leaching of K, Ca and Mg, in columns of a Red-Yellow Podzolic soil previously incubated with increasing doses of leaching with and without addition of N and P), was studied. The contents of K, Ca and Mg in the effluents, for each percolated volume, tended to increase as the dose of applied stillage, with and without NP, increased. In spite of the increase in K losses, the contents that remained, after leaching, in the upper, medium and lower thirds of the columns, were higher than the original soil content (0.17 mEq/100 g). For the highest level of applied stillage (400 m3/ha), with and without addition of N and P, and consequently, the highest dose of K. and for the highest volume of percolated water, the leached contents of Ca and Mg were about 0.5 mEq/100 g of soil. However, the percolated volumes of water for the soil treated with stillage, with and without addition of NP, showed that Mg was proportionally more leached than calcium.